Effect of platelet-rich plasma and bioactive glass in the treatment of intrabony defects - a split-mouth study in humans - Manmeet Kaur; T. Ramakrishnan; N. Amblavanan; Pamela Emmadi (Universidade Estadual de Campinas, 2015)
Aim: To compare the efficacy of platelet rich plasma (PRP) associated with bioactive glass (BG) and BG alone in the treatment of periodontal intrabony defects. Methods: Ten patients participated of the study. Using a split-mouth design, interproximal bony defects were surgically treated with either PRP/BG or BG alone. The clinical parameters plaque index, gingival index, gingival bleeding index, pocket probing depth (PPD), clinical attachment level (CAL) and gingival recession were recorded, and the defect fill was evaluated radiographically at baseline and 3 and 6 months after surgery. Results: At 6 months after therapy, the PRP/BG group showed mean PPD reduction of 3.4±1.4 mm, CAL mean gain of 4.3±1.3 mm, and defect fill of 3.5±1.0 mm. The BG group showed mean PPD reduction of 2.6±1.1 mm, mean CAL gain of 3.3±1.3 mm, and defect fill of 3.1±1.2mm. There was statistically significant greater PPD reduction at 3 months and CAL gain at 6 months for PRP/BG compared to BG alone, but no significant difference was observed in defect fill. Conclusions: Both therapies resulted in significant PPD reduction, CAL gain and defect fill. The association of PRP with a BG graft material seemed to add some benefits to the improvement of the clinical parameters in the treatment of intrabony defects.